Air pollution and telomere length in adults: A systematic review and meta-analysis of observational studies. (January 2019) - Miri, Mohammad; Nazarzadeh, Milad; Alahabadi, Ahmad; Ehrampoush, Mohammad Hassan; Rad, Abolfazl; Lotfi, Mohammad Hassan; Sheikhha, Mohammad Hassan; Sakhvidi, Mohammad Javad Zare; Nawrot, Tim S.; Dadvand, Payam
Abstract: Telomere length (TL) has been suggested to be a surrogate for cellular ageing, and a record of cumulative inflammation and oxidative stress over life. An emerging body of evidence has associated exposure to air pollution to changes in TL. To date there is no available systematic review of literature on this association. We aimed to systematically review and conduct meta-analysis of published studies on the relationship between air pollution and TL in adults. Electronic databases were systematically searched for available English language studies on the association between air pollution and TL published up to 1 July 2018. Meta-analyses were conducted following MOOSE guidelines. The heterogeneity in the reported associations was assessed using Cochran's Q test and quantified as I 2 index. Publication bias was assessed using Egger's regression. Our search identified 19 eligible studies including 11 retrospective and eight prospective studies of which, four had excellent quality, ten had good quality and five had fair quality. Meta-analysis result of two studies on long-term exposure to PM2.5 showed an inverse association between these exposures and TL (for 5 μg/m 3 PM2.5 –0.03 95% CI; −0.05,  −0.01). Meta-analysis of short-term exposure to PM2.5 with three studies and Polychlorinated Biphenyls (PCBs) with two studies revealed a direct association between these exposures and TL (0.03 95% CI; 0.02, 0.04 and 0.10 95% CI; 0.06, 0.15 respectively). No statistically significant relationship between exposure to PM10 and polycyclic aromatic hydrocarbons (PAHs) exposure and TL were observed. We observed suggestive evidence for associations between air pollution and TL with potentially different direction of associations for short- and long-term exposures. Graphical abstract: Image 1 Highlights: We reviewed evidence on the association of air pollution with telomere length (TL). 18 studies including 11 retrospective and seven prospective studies were identified. PAH exposure and long-term PM2.5 exposure were inversely associated with TL. PCBs exposure and short-term PM2.5 exposure were directly associated with TL. Abstract : While long-term PM2.5 exposure were inversely associated with telomere length, PCBs and short-term PM2.5 exposure were directly associated with telomere length.